The Manifest as a Text Modelling the Literary Field and its Perception - SIMYAN, TIGRAN (Bulletin of Yerevan University B: Philology, 2021)
The article examines the perceptions of the manifest in literary criticism of the Soviet period. The author tries to trace the perception of manifest in dictionaries, textbooks, literary dictionaries, anthologies diachronically. This approach makes it possible to trace the logic of understanding the manifest as a genre from the Soviet period to the present day.Particular attention is given to the problem of the origin of a manifest as a genre, a functional understanding of the manifest in the literary field (P. Bourdieu) and its communicative features.
Keywords: manifest, criticism understanding of manifest, genre of manifest, function of manifest